Impact of Inoculant Sources on Feed in Vitro Fermentability and Digestibility : Dampak Cairan Rumen Sumber Inokulan pada Fermentabilitas dan Kecernaan Pakan secara In Vitro (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2020)
The aim of this research is to compare alternative inoculant source for in vitro rumen fermentation. In the first experiment, inoculant from fistulated cattle kept in LIPI and IPB (Fis1 and Fis2) and inoculant from Bogor municipality abattoir and IPB abattoir (Abo1 and Abo2) were tested for their pH, total bacterial count, and protozoal number using a complete block design with four replications. In the second experiment, the effect of the inoculant sources was tested on cornmeal (F1), soybean oil meal (F2), Napier grass (F3), and dairy cattle complete ration (F4) fermentability and digestibility including pH, VFA, NH3, IVDMD and IVOMD parameters. The results showed an unsignificant different protozoal number among inoculant sources. The pH of Fis2 rumen liquor was significantly lower (p